2022
DOI: 10.3389/fcvm.2021.818215
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Clinical Outcomes Between Ticagrelor and Clopidogrel in Acute Coronary Syndrome: A Comprehensive Meta-Analysis

Abstract: BackgroundTicagrelor is currently recommended for patients with the acute coronary syndrome (ACS). However, recent studies have yielded controversial results.ObjectiveTo compare the clinical outcomes between ticagrelor and clopidogrel in patients with ACS.MethodsThree electronic databases were queried until April 25, 2021. We defined major adverse cardiovascular events (MACEs) as the primary efficacy endpoint. The secondary efficacy endpoints included stroke, stent thrombosis, cardiovascular death, all-cause d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 58 publications
(57 reference statements)
1
8
0
2
Order By: Relevance
“…Findings in the present study resulted in a decrease in the MACE, although this decrease was not statistically signi cant. A meta-analysis that included studies with ACS patients did not prove the superiority of Ticagrelor over Clopidogrel in this outcome (53). This is notable that since there is a possibility of bleeding and upper gastrointestinal complications in patients who receive the combination of Clopidogrel and Aspirin, these patients are prescribed drugs such as proton-pump inhibitors such as pantoprazole, which reduces the risk of bleeding by protecting the digestive tract mucosa, simultaneously (54).…”
Section: Discussionmentioning
confidence: 91%
“…Findings in the present study resulted in a decrease in the MACE, although this decrease was not statistically signi cant. A meta-analysis that included studies with ACS patients did not prove the superiority of Ticagrelor over Clopidogrel in this outcome (53). This is notable that since there is a possibility of bleeding and upper gastrointestinal complications in patients who receive the combination of Clopidogrel and Aspirin, these patients are prescribed drugs such as proton-pump inhibitors such as pantoprazole, which reduces the risk of bleeding by protecting the digestive tract mucosa, simultaneously (54).…”
Section: Discussionmentioning
confidence: 91%
“…Recent studies have shown that ticagrelor is associated with a significantly higher risk of dyspnea, major bleeding, and bradycardia events than clopidogrel. [16][17][18][19][20] And the compliance with ticagrelor in patients has also been shown to be lower than that with clopidogrel, which also brought challenges to the long-term treatment of ticagrelor.…”
Section: Discussionmentioning
confidence: 99%
“…Многочисленные исследования реальной клинической практики демонстрируют весьма противоречивые результаты в отношении сравнительной эффективности и безопасности клопидогрела и более мощных блокаторов рецепторов P2Y12 [8,9]. Часть из них не подтверждает преимуществ тикагрелора и прасугрела в отношении ишемических событий в рутинной практике.…”
Section: приверженность к терапии блокаторами рецепторов P2y12 побочн...unclassified
“…Поскольку клопидогрел последовательно демонстрировал наиболее благоприятный профиль безопасности из всех блокаторов рецепторов P2Y12 в рандомизированных исследованиях, метаанализах [26] и исследованиях реальной клинической практики [28], именно этот препарат рекомендуют выбирать эксперты Европейского общества кардиологов (ЕОК) у пациентов с ОКС без подъема сегмента ST и высоким риском кровотечений [15]. В рекомендациях 2020 г. предложен четкий алгоритм выбора режима антиагрегантной терапии в зависимости от риска кровотечений.…”
Section: пациенты с окс без подъема сегмента St с высоким и очень выс...unclassified